Implementation of Character Education through Project Activities Expo in the Emancipated Curriculum Based on Sundanese Culture at Junior High Schools - Indah Al Aziz; Ropiah Tul’adawiyah; Yeni Rachmawati (Yayasan Keluarga Guru Mandiri, 2024)
This research aims to explore and analyze the implementation of character education through the emancipated curriculum (Kurikulum Merdeka) project activities expo based on local Sundanese culture at Junior High Schools (SMP). The research method used a phenomenological approach with interpretive qualitative research that looks and hears more closely and in detail from individual explanations and understanding of their experiences. Participants in this research include students and teachers involved in project activities expo. Data was collected through observation, interviews, and document analysis. The findings show that the effectiveness of the emancipated curriculum expo project is rooted in local Sundanese cultural wisdom in implementing character education in junior high schools. Developing projects, assigning roles, and exhibiting students' work is essential to holistic character formation. In addition, these activities strengthen students' cultural identity and increase their involvement in the learning process. The implications of these findings emphasize the importance of integrating locally based character education in the school curriculum to strengthen students' cultural and moral awareness in the era of globalization. This research contributes to advancing knowledge by highlighting the significance of culturally rooted character education initiatives in enhancing students' holistic development in educational contexts. As a result, students can work together in teams, reason critically, be creative, have a sense of diversity, and respect opinions.